Features of the tourist enterprises image formation - Z. V. Kushkhova; O. L. Ryvkina; N. I. Khrabrova (Управление)
The article defines the types of tourist enterprises depending on the duration of operation on the market and the features of activities to maintain and develop their image based on the empirical data obtained as a result of the tourist services market research in Yalta (Republic of Crimea). These are enterprises that are that for the first time begin to operate in the tourist market and form their image, enterprises that are active in the market, but do not form their image; enterprises that need to review or completely change their image building activities.For each type of enterprise, the stages of the image formation, including the necessary marketing tools, have been developed and substantiated: for the first type of the enterprises – determination of the image audience, development and approval of corporate identity, implementation of internal and external image building, image management; for the second type – image audit, analysis of the causes of the loyalty loss, development and implementation of image events; for the third type – image audit, choice of approach to the image program implementation. It is proved that the image of the tourist enterprise is characterized by a life cycle.It is proposed to consider four stages of the life cycle: formation; development; stability; blurring and loss. The characteristic features of the stages, management goals and the program of image building events have been determined.